2017
DOI: 10.1107/s2053229617007616
|View full text |Cite
|
Sign up to set email alerts
|

A charge-transfer salt composed of methyl viologen and hexacyanidoferrate(II)

Abstract: The methyl viologen dication, used under the name Paraquat as an agricultural reagent, is a well-known electron-acceptor species that can participate in charge-transfer (CT) interactions. The determination of the crystal structure of this species is important for accessing the CT interaction and CT-based properties. The title hydrated salt, bis(1,1'-dimethyl-4,4'-bipyridine-1,1'-diium) hexacyanidoferrate(II) octahydrate, (CHN)[Fe(CN)]·8HO or (MV)[Fe(CN)]·8HO [MV is the 1,1'-dimethyl-4,4'-bipyridine-1,1'-diium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The diffuse-reflectance spectra of 1-Wet and 1-Dry are shown in Figure . It is known that CT salts composed of viologen and [Fe­(CN) 6 ] 4– display absorption bands in the visible region that correspond to intermolecular CT transition; ,, 1-Wet and 1-Dry exhibit absorption bands at 560 and 507 nm, respectively, which we assign to their intermolecular CT transitions. The band shift observed as 1-Wet transformed into 1-Dry suggests that each crystal phase exhibits different intermolecular CT interactions.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The diffuse-reflectance spectra of 1-Wet and 1-Dry are shown in Figure . It is known that CT salts composed of viologen and [Fe­(CN) 6 ] 4– display absorption bands in the visible region that correspond to intermolecular CT transition; ,, 1-Wet and 1-Dry exhibit absorption bands at 560 and 507 nm, respectively, which we assign to their intermolecular CT transitions. The band shift observed as 1-Wet transformed into 1-Dry suggests that each crystal phase exhibits different intermolecular CT interactions.…”
Section: Resultsmentioning
confidence: 90%
“…Charge-transfer (CT) salts are known to exhibit physical properties based on intermolecular CT interactions, such as electric conduction and magnetism, among others. The salt of methyl viologen (MV 2+ , 1,1′-dimethyl-4,4′-bipyridine-1,1′-diium) and hexacyanidoferrate­(II), (MV) 2 [Fe­(CN) 6 ]·8H 2 O, is one such CT salt. In Prussian blue, one of the most famous intervalence CT compounds, the [Fe­(CN) 6 ] 4– species acts as the electron-donor, while MV 2+ is a well-known electron-acceptor that readily forms intermolecular CT compounds with electron-donating species . While both [Fe­(CN) 6 ] 4– and MV 2+ ions are colorless, the CT salt of MV 2+ and [Fe­(CN) 6 ] 4– exhibits deep colors based on CT interactions; deep blue in the solid phase and red-purple in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the vast number of applications of viologens, it is important to analyze the crystal structures of viologens to assess the important information about charge transfer interaction, distance between the electron donor and acceptor, packing of cations and anions in the molecule and its effect on fluorescence, photoswitching properties. Very few studies have been reported on the X-ray diffraction analysis of these molecules [17] [18] [19] [20]. Herein, we report the synthesis, crystal structure and photophysical properties of N,N'-dimethyl-2,5-Bis(pyridinium)oxadiazole 4 and its precursor 2,5-Bis(pyridine)oxadiazole 2.…”
Section: Introductionmentioning
confidence: 98%